The development of the Dutch "National model integrated care for childhood overweight and obesity" - J. Halberstadt; L. W. Koetsier; M. Sijben; J. Stroo; M. van der Velde; E. G. A. H. van Mil; J. C. Seidell (BMC, 2023)
Abstract Background Childhood obesity is a chronic disease with negative physical and psychosocial health consequences. To manage childhood overweight and obesity, integrated care as part of an integrated approach is needed. To realise implementation of this integrated care, practical guidance for policy and practice is needed. The aim of this study is to describe the development of a Dutch national model of integrated care for childhood overweight and obesity and accompanying materials for policy and practice. Methods The development of the national model was led by a university-based team in collaboration with eight selected Dutch municipalities who were responsible for the local realisation of the integrated care and with frequent input from other stakeholders. Learning communities were organised to exchange knowledge, experiences and tools between the participating municipalities. Results The developed national model describes the vision, process, partners and finance of the integrated care. It sets out a structure that provides a basis for local integrated care that should facilitate support and care for children with overweight or obesity and their families. The accompanying materials are divided into materials for policymakers to support local realisation of the integrated care and materials for healthcare professionals to support them in delivering the needed support and care. Conclusions The developed national model and accompanying materials can contribute to improvement of support and care for children with overweight or obesity and their families, and thereby help improve the health, quality of life and societal participation of these children. Further implementation of the evidence- and practice-based integrated care while evaluating on the way is needed.